Predation of 'Aonidiella aurantii' (Maskell) crawlers by phytoseiids - Urbaneja, Alberto; Juan-Blasco, María; Verdú, María J. (2017)
For our knowledge, there are few studies about the role of phytoseiids (Acari: Phytoseiidae) preying on Aonidiella aurantii (Maskell) (Hemiptera: Diaspididae) crawlers. The aims of the present work were to study in laboratory the development of three of the most abundant phytoseiids in Spanish citrus, Euseius stipulatus (Athias-Henriot), Neoseiulus californicus (McGregor) and Typhlodromus phialatus Athias-Henriot, and Amblyseius swirskii AthiasHenriot, recently introduced and released in Spain, feeding exclusively on A. aurantii crawlers. Furthermore, the ability of A. swirskii to reduce A. aurantii infestation on young citrus plants was studied under semi-field conditions by means of augmentative releases of this phytoseiid. E. stipulatus was the only phytoseiid species tested which was not able to lay eggs on this prey. The progeny of N. californicus were not able to reach the protonymphal stage. On the other hand, T. phialatus and A. swirskii completed their development, from egg to adult preying exclusively on this prey. In the semi-field experiments, several doses of A. swirskii were tested. Once the phytoseiids were installed on the young trees, an artificial infestation of A. aurantii crawlers was promoted on each citrus plant. A significant reduction in A. aurantii infestation was observed in the trees where A. swirskii was previously released.